Enhancing Managerial Performance Through Accounting Information Systems and Performance Measurement - Arief, M; Zahara, Zahara; Ramadhea. Jr, Syafira (Economics, Business, Accounting & Society Review, 2026)
Managerial performance in public sector organizations has become an important indicator for evaluating the effectiveness of government administration and the quality of public services. In recent years, the implementation of accounting information systems and structured performance measurement systems has increasingly been recognized as a strategic mechanism for improving organizational performance and managerial decision-making in government institutions. This study aims to examine the influence of accounting information systems and performance measurement systems on managerial performance in the Regional Work Units (SKPD) of Bukittinggi City. This research adopts a quantitative, causal approach, using primary data collected through questionnaires distributed to officials involved in financial and managerial activities within SKPD. The study employs total sampling, covering 28 SKPD, and analyzes 81 valid responses using multiple linear regression. The results indicate that accounting information systems have a positive, significant effect on managerial performance by providing relevant, timely information that supports decision-making. Furthermore, performance measurement systems also demonstrate a significant positive influence on managerial performance, indicating that systematic performance evaluation mechanisms can strengthen managerial accountability and improve organizational effectiveness. This study provides empirical evidence on the integration of accounting information systems and performance measurement systems to improve managerial performance in the local government context. The findings imply that strengthening information systems and performance evaluation mechanisms can enhance managerial effectiveness and support better governance practices in public sector organizations.